A comparative study on the abundance and elemental composition of POM in three interconnected basins: the Black, the Marmara and the Mediterranean Seas - COBAN-YILDIZ, Y.; TUGRUL, S.; EDIGER, D.; YILMAZ, A.; POLAT, C. (Mediterranean Marine Science, 2000)
The abundance and elemental composition of suspended particulate organic matter in the upper layers of the interconnected Mediterranean, Marmara and Black Seas having different ecosystems were determined in 1990-1998. The aim was principally to compare the C:N:P ratio of seston and understand factors controlling the seston composition in near- and off-shore waters of these seas. In the Marmara Sea, euphotic zone average particulate concentrations varied regionally and seasonally between 10-35 ìM for POC, 0.4-4.5 ìM for PON and 0.05-0.45 ìM for PP. These concentrations are mostly above the off-shore Black Sea values but much greater than those measured in the open waters of the north-eastern Mediterranean whose near-shore data are comparable with the seston content of the deep Black Sea. Comparison of C:N:P ratios of seston reveals that atmospheric and land-based phosphorus input influences the C:P and N:P ratios in the near-shore waters. Apparent nutrient deficiencies observed in the water column were not as remarkable in the elemental composition of seston. Unexpectedly, in the NE Mediterranean, N:P ratios from regression analyses of particulate data are very low (7-9) in the coastal region but slightly increase to levels of 10-15 in the open sea. In the Sea of Marmara, the N:P ratios (7-12) of seston are as low as in the Mediterranean, being consistent with the particulate ratios of the Black Sea inflow and NO3:PO4 ratios of the Marmara sub-halocline water. The Black Sea seston is relatively rich in carbonaceous compounds with N:P ratio ranging merely between 15-17 in the open sea but 9-27 in coastal waters where riverine discharges markedly influence the stoichiometry of seston.